2014
DOI: 10.1088/1752-7155/8/4/046006
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin as an epithelial barrier protein in exhaled breath condensate

Abstract: Airway epithelium plays an important role as a physical barrier and a modulator of allergic response. Junctions between cells provide epithelial integrity and barrier function. The aim of this study was to investigate the influence of atopy on airway epithelial integrity in asthma and to measure E-cadherin levels in exhaled breath condensate as an indicator epithelial damage. A total of 74 patients with asthma (35 atopic and 39 non-atopic) and 39 healthy children were enrolled in this case-control study. Socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…In biopsies of the bronchial mucosa of patients with atopic asthma, E-cadherin levels in the respiratory epithelia were shown to be lower than non-atopic and non-asthmatic cases (17,44,45). Similarly, a study published by our group showed that patients with asthma had lower levels of E-cadherin in their airways (46). Similar to previous studies, the present study suggested that E-cadherin and β-catenin levels were lower in asthmatic model mice.…”
Section: Discussionsupporting
confidence: 89%
“…In biopsies of the bronchial mucosa of patients with atopic asthma, E-cadherin levels in the respiratory epithelia were shown to be lower than non-atopic and non-asthmatic cases (17,44,45). Similarly, a study published by our group showed that patients with asthma had lower levels of E-cadherin in their airways (46). Similar to previous studies, the present study suggested that E-cadherin and β-catenin levels were lower in asthmatic model mice.…”
Section: Discussionsupporting
confidence: 89%
“…A variety of allergens and stimuli, except probiotics, are detrimental to the host. After prolonged and/or extensive exposure to ozone, house dust mite (HDM), bacteria and viruses, etc., epithelial structural proteins such as E‐cadherin and zonula occludens‐1 (ZO‐1) were destructed, resulting in decreased epithelial tightness and barrier damage 1‐4 . The dysfunction of epithelia is a common pathological characteristic of mucosal diseases.…”
Section: Mucosal Barrier Acts More Than a Physical Barriermentioning
confidence: 99%
“…After prolonged and/or extensive exposure to ozone, house dust mite (HDM), bacteria and viruses, etc., epithelial structural proteins such as E‐cadherin and zonula occludens‐1 (ZO‐1) were destructed, resulting in decreased epithelial tightness and barrier damage. 1 , 2 , 3 , 4 The dysfunction of epithelia is a common pathological characteristic of mucosal diseases. Various degrees of epithelial damage are the key determinant of mucosal diseases such as asthma, chronic obstructive pulmonary disease (COPD) and inflammatory bowel diseases (IBD) and the degree of epithelial damage is positively correlated with the severity of diseases.…”
Section: Mucosal Barrier Acts More Than a Physical Barriermentioning
confidence: 99%
“…This may make the respiratory epithelial cells of asthma patients more sensitive to allergens. 35,36,62,69 In the early 1990s, ultrastructural studies showed that asthmatic patients had fewer intercellular adhesion junction complexes compared with nonasthmatic patients, but the underlying mechanisms of these structural differences remain to be clarified. 18 Disruption of epithelial barrier function has presumed consequences such as easier penetration of inhaled allergens into respiratory tissue, increased allergen access to antigen-presenting cells in the submucosa, and greater extension of spasmogenic agonists to smooth muscles.…”
Section: Asthmamentioning
confidence: 99%